A COMPARATIVE ANALYSIS OF DETERMINANTS OF ISLAMIC AND CONVENTIONAL BANKING PERFORMANCES IN INDONESIA - Sri Ulina; M. Shabri Abd Majid (AMWALUNA (Jurnal Ekonomi dan Keuangan Syariah), 2020)
This study attempts to explore comparatively the determinants of financial performances between the conventional and Islamic banks in Indonesia. The determinants investigated in the study include liquidity, non-performing financing, capital adequacy, and operational cost. The samples of this study are three state-owned conventional banks and three Islamic banks that were selected by the purposive sampling technique. Based on the panel regression analysis, the study found that, for the conventional banks, capital adequacy, liquidity, and operational cost had significant influences on banks' performances, while the non-performing loan had an insignificant effect. On the other hand, for the Islamic banks, the liquidity, non-performing financing, and operational cost had significant influences on banks’ performance, while capital adequacy had an insignificant effect. These findings provide important implications for the respective banks to design a proper financial policy to enhance their performances by focusing on the significant determinants affecting banks' performances.